Effectiveness of Endophytic Bacteria Rhizophora sp. from Mangrove Plants to Control Root-Knot Nematodes (Meloidogyne spp.). - Nurdiah Khasanah; Safira Rizka Lestari; Dita Megasari (The University of Lampung, 2025)
Meloidogyne spp. is a root-knot nematode that can cause damage to plants up to 68%. The common control is the use of pesticides, but in the long term, it can damage the soil, so it is necessary to use biological agents that can control Meloidogyne spp. without causing environmental damage. The purpose of this study was to determine the ability of endophytic bacteria to control root-knot nematodes Meloidogyne spp.. The method used in this study was the exploration of endophytic bacteria from the Wonorejo mangrove ecotourism area, Surabaya using purposive sampling method. The five best endophytic bacteria were tested further with antagonistic tests. This test was carried out in vitro using 3 concentrations, namely 106, 108, and 1010 CFU/ml with 3 repetitions. The obtained results were tested using probit analysis to obtain the LC50 values. It was found that LC50 values for the most effective concentration to kill 50% of the Meloidogyne sp population is 109 and 1010 CFU/ml. It was also revealed that the isolate that is most capable of controlling Meloidogyne spp. nematodes is isolate A43. Keywords: Antagonist test, Endhopic bacteria, LC50, Mangrove, Meloidogyne spp.